DNA barcoding reveals chaotic labeling and misrepresentation of cod (鳕, Xue) products sold on the Chinese market. (February 2016) - Xiong, Xiong; Guardone, Lisa; Giusti, Alice; Castigliego, Lorenzo; Gianfaldoni, Daniela; Guidi, Alessandra; Andrea, Armani
Abstract: The increasing rate of seafood frauds, especially in the case of highly priced species, highlights the need of verifying the identity of fish products. This paper describes the application of DNA barcoding to the identification of 52 products commercialized with the Chinese term 鳕 ( Xue, Cod) in supermarkets (Nanjing and Shanghai) and in the online market. Considering the lack of harmonization around the definition of Cod, the mislabeling rate was assessed according to three increasingly stringent definitions: Cod meaning Gadiformes species; Cod meaning Gadus spp.; Cod not meaning any specific species, since a qualifier ("Atlantic", "Pacific" or "Greenland") should be added in order to refer to Gadus morhua, Gadus macrocephalus or Gadus ogac, respectively. Results highlighted a very high mislabeling rate, which exceeded 60% even with the less stringent definition. Interestingly, only 42.3% of the samples were Gadiformes, while the others were Perciformes, Pleuronectiformes or toxic Tetraodontiformes species. Economic, ecological and health issues arising from the misuse of the term Cod are discussed in the light of the leading role of China in the seafood worldwide industry and of the increased national consumption of marine species. Highlights: DNA barcoding was used to evaluate the identity of fish sold as 鳕 ( Xue  = cod). Fish samples were purchased in supermarkets (Nanjing and Shanghai) and online. An impressive mislabeling rate, always standing over 60%, was discovered. Perciformes, Pleuronectiformes and toxic pufferfish were sold under the name Xue . Economic, ecological and health issues arise from the misuse of the term cod.